Classification And Recognition Of Petroglyphs Using “Artificial Intelligence” - Tokhatyan, Karen; Ugujyan, Andranik (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The reliability of historical and cultural primary sources, and hence the scientific value, depends on the degree of study. In the case of a huge number and variety of petroglyphs and related cultural artifacts, it is necessary to conduct a complex, multifaceted classification which will facilitate the extraction of functions, semantic and spatio-temporal aspects of the petroglyphs. Modern Machine Learning (ML) technologies are also applicable in Petroglyphology. Their contribution is promising in the problems of image recognition and classification.
Keywords: History